2017
DOI: 10.1371/journal.pone.0182795
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of pre-operative motor dysfunction from gliomas in the region of corticospinal tract: Evaluation with diffusion tensor imaging

Abstract: Background and purpose

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 36 publications
0
19
0
3
Order By: Relevance
“…Binding of IgM and IgG was assessed as the relative geometric mean (rGM), calculated by dividing the geometric mean fluorescence for each sample by that of the negative control, as previously described. 7 , 13 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of IgM and IgG was assessed as the relative geometric mean (rGM), calculated by dividing the geometric mean fluorescence for each sample by that of the negative control, as previously described. 7 , 13 …”
Section: Methodsmentioning
confidence: 99%
“… 4 6 However, like pigs, Old World NHPs express N-glycolylneuraminic acid (Neu5Gc), and therefore do not develop natural anti-Neu5Gc antibodies. 7 If the CMP-N-acetylneuraminic acid hydroxylase (CMAH) gene is knocked out (resulting in deletion of expression of Neu5Gc), as in TKO pigs, this appears to expose 1 or more new xenoantigens on the pig cells (the so-called “fourth xenoantigen”). 8 In contrast, if CMAH is not knocked out (eg, in α1,3-galactosyltransferase gene-knockout [GTKO] and GTKO/β-1,4 N-acetylgalactosaminyltransferase gene-knockout [β4GalNT2KO] pigs), the pig appears not to express the “fourth antigen” (or expresses it at a lower level).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the white matter tracts in 17 glioma-bearing rats were classified according to the criteria of displacement, infiltration and disruption (Gao et al, 2017; Witwer et al, 2002) as follows: (1) grade 1: displaced and edematous if the tracts displayed a normal anisotropy signal relative to the corresponding tracts in the contralateral hemisphere, displacement of the fibers by the tumor and some peritumoral edema delineated by the DTT imaging (Fig. S1).…”
Section: Methodsmentioning
confidence: 99%
“…Rosenstock et al (2017) showed that the FA value were lower and the ADC value were higher in peritumoral areas, which indicated that the FA and ADC value were affected at the peritumoral level. Additionally, tumor cell proliferation and invasion could result in a disruption of CST, and the degree of injury may reflect its biological behavior (Gao et al, 2017; Painter & Hillen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Various ROIs can be used to track CST, resulting in high variability rate. Weiss et al showed that an ROI set at the anterior inferior pontine region yielded better tracking results compared to the ROI set at the internal capsule [28][29][30]. Furthermore, CST was reconstructed from neural bundles passing through by cerebral peduncle, posterior limb of internal capsule and corona radiata in a patient after stroke [31].…”
Section: Corticospinal Tractmentioning
confidence: 99%